2014
DOI: 10.1128/aem.01940-14
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Pseudomonas taiwanensis VLB120 for Constitutive Solvent Tolerance and Increased Specific Styrene Epoxidation Activity

Abstract: The application of whole cells as biocatalysts is often limited by the toxicity of organic solvents, which constitute interesting substrates/products or can be used as a second phase for in situ product removal and as tools to control multistep biocatalysis. Solvent-tolerant bacteria, especially Pseudomonas strains, are proposed as promising hosts to overcome such limitations due to their inherent solvent tolerance mechanisms. However, potential industrial applications suffer from tedious, unproductive adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 69 publications
5
69
1
Order By: Relevance
“…The biofilm grown in three-phase aqueous-air-organic segmented flow exhibited enhanced tolerance compared to their suspended counterpart [14] and also displayed stable catalytic activities for longer period of time. Overall, this biofilm reactor is a promising format to perform catalysis involving toxic and poorly water soluble compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biofilm grown in three-phase aqueous-air-organic segmented flow exhibited enhanced tolerance compared to their suspended counterpart [14] and also displayed stable catalytic activities for longer period of time. Overall, this biofilm reactor is a promising format to perform catalysis involving toxic and poorly water soluble compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, organic compounds having logP o/w values (partition coefficient of a compound in an equimolar mixture of octanol and water) between 1 and 4 are considered to be toxic because they might interfere with the cellular membrane and disturb the physiological and functional integrity of the active cell [13]. While it was possible to grow biofilms in minimal medium under these conditions, the planktonic counterparts of Pseudomonas taiwanensis VLB120∆C needs complex nutrients such as yeast extracts or tryptone to support growth in the presence of a second phase of styrene 1% (v/v) [14]. The most favorable option to overcome substrate solubility and toxicity issues is to apply a second organic phase which acts as a substrate carrier phase to partition the substrate concentration below the toxicity limit and to deliver it continuously [7].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Pseudomonas taiwanensis VLB120, from which SMOcoding genes were isolated, is well known as a solvent-tolerant microorganism. Volmer et al reported that the depletion of ttgV, which encodes a transcriptional repressor of solvent efflux pump gene expression, increased the solvent tolerance of P. taiwanensis VLB120 and biocatalytic activity of the epoxidation of styrene (37). This suggested that using organic solvent-tolerant microorganisms as heterologous expression hosts for RhSMO genes is a suitable strategy for improving our biocatalytic system for producing optically pure straight-chain (S)-epoxyalkanes.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the SMO from Pseudomonas taiwanensis VLB120 (Volmer et al 2014) has been successfully scaled up in the production of enantiopure (S)-styrene oxide (Panke et al 2002). Further investigation Open Access *Correspondence: wuzhl@cib.ac.cn 1 Key Laboratory of Environmental and Applied Microbiology, Chengdu Institute of Biology, Chinese Academy of Sciences, 9 South Renmin Road, 4th Section, Chengdu 610041, Sichuan, People's Republic of China Full list of author information is available at the end of the article has expanded its substrate spectrum to styrene derivatives and analogs (Lin et al 2011c;Liu et al 2015), as well as aliphatic olefins (Toda et al 2015).…”
Section: Introductionmentioning
confidence: 99%